The puzzle of HD 104994 (WR 46) - Marchenko, Sergey V. (2000)
Intense coordinated spectroscopic and photometric monitoring of the suspected Wolf-Rayet binary WR 46 in 1999 reveals clear periodic variations, P = 0.329 ± 0.013 days, in the radial velocities of the emission lines of highest ionization potential, O VI and N V, found deepest in the Wolf-Rayet wind and thus least likely to be perturbed by a companion. These are accompanied by coherent variability in the profiles of lines with lower ionization/excitation potential and in the continuum flux. Most probably originating from orbital motion of the Wolf-Rayet component of the binary, this periodic radial velocity signal disappears from time to time, thus creating a puzzle yet to be solved. We show that the entangled patterns of the line profile variability are mainly governed by transitions between high and low states of the system's continuum flux.